Tegretol (Carbamazepine) Effect on the Morphometric Assay of Liver in Female White Mice (Mus musculus) - Jaber, Nawar R.; Al-Bakri, Nahla A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Carbamazepine (CBZ) is one of many anticonvulsants used to treat trigeminal neuralgia and epilepsy. Antiepileptic drugs (AED`s) are the second most important class of medications that lead to hepatotoxicity and induced liver injury, this study was conducted to evaluate the effects of CBZ on the liver. A total of 40 female mice were taken and divided into four groups (A/treated for 14 days, B/ control, C/ treated for 30 days, D/ control), the drug was given as an oral suspension formula 100mg/5ml at dose 20 mg/kg/mouse via gastric gavage daily for 14 and 30 days. Statistical analysis revealed that there were no significant differences in the white female mice body weight (P>0.05) in the treated group for 14 days as well as the treated group for 30 days, but there were significant differences between the treated groups studied. Statistical analyses result of liver weight, hepatocytes diameter, central vein and portal vein diameters showed significant differences in the treated group for 14 days (P<0.05) as well as the treated group for 30 days, and there were significant differences between all treated groups studied. The study concluded that carbamazepine (CBZ) can had no effect on body weight but it can induce several hepatic changes if it used on a short or long terms, therefore, it was advised to take cautions when describing this drug.